Deep (Meta)genomics and (Meta)transcriptome Analyses of Fungal and Bacteria Consortia From Aircraft Tanks and Kerosene Identify Key Genes in Fuel and Tank Corrosion - Krohn, Ines; Bergmann, Lutgardis; Qi, Minyue; Indenbirken, Daniela; Han, Yuchen; Perez-Garcia, Pablo; Katzowitsch, Elena; Hägele, Birgit; Lübcke, Tim; Siry, Christian; Riemann, Ralf; Alawi, Malik; et al. (Frontiers in Microbiology, 2021)
Microbial contamination of fuels, associated with a wide variety of bacteria and fungi, leads to decreased product quality and can compromise equipment performance by biofouling or microbiologically influenced corrosion. Detection and quantification of microorganisms is critical in monitoring fuel systems for an early detection of microbial contaminations. To address these challenges, we have analyzed six metagenomes, one transcriptome and more than 1,200 fluid and swab samples taken fuel tanks or kerosene. Our deep metagenome sequencing and binning approaches in combination with RNA-seq data and qPCR methods implied a metabolic symbiosis between fungi and bacteria. The most abundant bacteria were affiliated with the α-, β-, and γ-Proteobacteria, and the filamentous fungi Amorphotheca. We identified a high number of genes, which are related to kerosene degradation, and biofilm formation. Surprisingly a large number of genes coded enzymes involved in for polymer degradation and potential bio-corrosion processes. Thereby the transcriptionally most-active microorganisms were affiliated with the genera of the Methylobacteria, Pseudomonas, Kocuria, Amorpotheka, Aspergillus, Fusarium and Penicillium. Many not yet cultured bacteria and fungi appeared to contribute to the biofilm transcriptional activities. The largest numbers of transcripts were observed for dehydrogenases, oxygenase, exopolysaccharide production, attachment and pili/flagellar associated proteins, efflux pumps and secretion systems as well as lipase and esterase activity.